2016
DOI: 10.1371/journal.pone.0155375
|View full text |Cite|
|
Sign up to set email alerts
|

Warming and Nitrogen Addition Alter Photosynthetic Pigments, Sugars and Nutrients in a Temperate Meadow Ecosystem

Abstract: Global warming and nitrogen (N) deposition have an important influence on terrestrial ecosystems; however, the influence of warming and N deposition on plant photosynthetic products and nutrient cycling in plants is not well understood. We examined the effects of 3 years of warming and N addition on the plant photosynthetic products, foliar chemistry and stoichiometric ratios of two dominant species, i.e., Leymus chinensis and Phragmites communis, in a temperate meadow in northeastern China. Warming significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Also, warming had no significant effect on C:N and C:P ratios in bulk soil (Figure 3). Our result was consistent with the findings of previous studies conducted in other grassland ecosystems (Wang et al 2014, Yu et al 2014, Zhang et al 2015, 2016 Aggregates size class (mm) ratios to warming in the alpine meadow ecosystem were of importance for ecological stability in this region under climate warming scenario. In the previous studies (Wang et al 2014, Yu et al 2014, changes in biotic (e.g., vegetation biomass, microbial activity) and abiotic factors (e.g., soil moisture, elevational gradient) were considered to be responsible for the insignificant changes of soil nutrients.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Also, warming had no significant effect on C:N and C:P ratios in bulk soil (Figure 3). Our result was consistent with the findings of previous studies conducted in other grassland ecosystems (Wang et al 2014, Yu et al 2014, Zhang et al 2015, 2016 Aggregates size class (mm) ratios to warming in the alpine meadow ecosystem were of importance for ecological stability in this region under climate warming scenario. In the previous studies (Wang et al 2014, Yu et al 2014, changes in biotic (e.g., vegetation biomass, microbial activity) and abiotic factors (e.g., soil moisture, elevational gradient) were considered to be responsible for the insignificant changes of soil nutrients.…”
Section: Resultssupporting
confidence: 92%
“…However, no consistent results have been presented so far. Some studies showed that warming did not affect soil organic carbon (OC), total N (TN), and total P (TP) contents (Wang et al 2014, Yu et al 2014, Zhang et al 2015, 2016, whereas other studies found that warming significantly decreased soil OC, TN and TP contents (Li et al 2011, Rui et al 2012, Alatalo et al 2017). Both biotic (e.g., vegetation biomass, microbial activity) and abiotic factors (e.g., soil moisture, elevational gradient) were considered to contribute to the contradictory findings (Wang et al 2014, Yu et al 2014.…”
mentioning
confidence: 99%
“…The possible reason might be that N deposition can further increase soil N availability and promote plant N uptake, leading to enhanced photosynthetic pigment synthesis (Zhang et al, 2013). Additionally, increase of chlorophyll suggested that N deposition could also promote photosynthesis (Zhang et al, 2016). The combined effects of warming and N deposition also significantly promoted the synthesis of photosynthetic pigments, while the impacts were not as stronger as warming alone.…”
Section: Warming and N Deposition Alter Leaf N Content And Thus Inflmentioning
confidence: 99%
“…N supplementation directly affects the photosynthetic pigment content in leaves as well as the activity of ribulose 1,5-bisphosphate carboxylase, the enzyme in leaves essential for atmospheric CO 2 fixation ( Makino et al 2000 ). Furthermore, soil acidification may lead to the adsorption of alkaline cations, disruption of nutrient balance and inhibition of photosynthesis ( Bergkvist and Folkeson 1992 ; Zhang et al 2016 ). The present work found that with a low level of N application in the absence of BC amendment, the photosynthetic pigments Car, Chla and Chlb increased, whereas a high level of N application suppressed the accumulation of the pigments.…”
Section: Discussionmentioning
confidence: 99%